Acceptance and commitment therapy adapted for women with infertility: a pilot study of the Infertility ACTion program - Ashley A. Balsom; Bridget Klest; Bethany Sander; Jennifer L. Gordon (BMC, 2024)
Abstract Background Approximately one in six couples are currently infertile, defined as unable to achieve pregnancy despite 12 or more months of active attempts to conceive. Experiencing infertility has been disproportionately associated with an array of psychological difficulties, particularly in women. However, currently available psychological interventions have had minimal benefits for distress, anxiety, or depression related to infertility. Methods A one-arm pilot study was conducted to test the acceptability of a newly created acceptance and commitment therapy-based self-guided program-Infertility ACTion. Twenty women, located in Canada, completed the program and completed measures assessing expectancy of improvement, treatment credibility, participant satisfaction, treatment completion and retention, psychological flexibility, fertility quality of life, depression, and anxiety. Participants were also asked to provide feedback on how the researchers could improve the intervention. Paired sample t-tests were conducted to compare pre- and post-intervention outcomes. Results Sixteen out of 20 participants completed the entire intervention. Reported treatment expectancy, credibility and satisfaction were favorable. Eighty-one percent of participants reported that they would recommend the program to a friend and 88% thought the program was worth their time. Medium increases in psychological flexibility and fertility quality of life were observed. Improvements in anxious and depressive symptoms were in the small to medium range but were not significant. Participants had several recommendations for program improvement. Conclusions This acceptance and commitment therapy-based self-guided program proved to be an acceptable treatment for infertility-related distress. Participant feedback will be used to adjust the current intervention in preparation for a more rigorous randomized-controlled trial testing this program.